(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The current trend in software development involves working remotely as a team, an individual, or even an organization. But because so many businesses operate internationally and the market is global, it's necessary to set up global virtual teams. Members of the global virtual team are progressively immersed in globalised business environments across organizational, temporal, and spatial boundaries thanks to information and communication technologies. The most crucial elements in the functioning of a global virtual team are information sharing, cooperation, and communication. This paper aims to address two research enquiries. Finding the variables influencing the performance of international virtual teams is the first research question. A careful examination of the literature was done in order to respond to the first research question. The ranking of the factors influencing the performance of global virtual teams in relation to their degree of influence is the subject of the second research question. An online survey was distributed to 100 developers and IT managers from eight different IT companies in order to answer the second research question. The data was analyzed using the Statistical Package for Social Science (SPSS 22). In this study, we looked into the variables that affect the performance of international virtual teams. These factors included disparities in culture, language, and time zones as well as team size, technical difficulties, a lack of trust, insufficient training, and ICT problems. The findings also indicated that insufficient training is the primary factor influencing the effectiveness of global virtual teams. Nonetheless, the size of the team has the least impact on the effectiveness of international virtual teams.